A Spontaneous Model of Experimental Autoimmune Encephalomyelitis Provides Evidence of MOG-Specific B Cell Recruitment and Clonal Expansion - Salvador, Florent; Deramoudt, Laure; Leprêtre, Frédéric; Figeac, Martin; Guerrier, Thomas; Boucher, Julie; Bas, Mathilde; Journiac, Nathalie; Peters, Anneli; Mars, Lennart T.; Zéphir, Hélène (Frontiers in Immunology, 2022)
The key role of B cells in the pathophysiology of multiple sclerosis (MS) is supported by the presence of oligoclonal bands in cerebrospinal fluid, by the association of meningeal ectopic B cell follicles with demyelination, axonal loss and reduction of astrocytes, as well as by the high efficacy of B lymphocyte depletion in controlling inflammatory parameters of MS. Here we use a spontaneous model of experimental autoimmune encephalomyelitis (EAE) to study the clonality of the B cell response targeting myelin oligodendrocyte glycoprotein (MOG). In particular, 94% of SJL/j mice expressing an I-As: MOG92-106 specific transgenic T cell receptor (TCR1640) spontaneously develop a chronic paralytic EAE between the age of 60-500 days. The immune response is triggered by the microbiota in the gut-associated lymphoid tissue, while there is evidence that the maturation of the autoimmune demyelinating response might occur in the cervical lymph nodes owing to local CNS drainage. Using MOG-protein-tetramers we tracked the autoantigen-specific B cells and localized their enrichment to the cervical lymph nodes and among the brain immune infiltrate. MOG-specific IgG1 antibodies were detected in the serum of diseased TCR1640 mice and proved pathogenic upon adoptive transfer into disease prone recipients. The ontogeny of the MOG-specific humoral response preceded disease onset coherent with their contribution to EAE initiation. This humoral response was, however, not sufficient for disease induction as MOG-antibodies could be detected at the age of 7 weeks in a model with an average age of onset of 197 days. Questioning whether EAE onset would be accompanied by affinity maturation of the MOG-specific B cell response we FACS-sorted MOG-tetramer binding cells and clonally expand them in vitro to sequence the paratopes of the IgG heavy chain and kappa light chains. Despite the fragility of clonally expanding MOG-tetramer binding effector B cells, our results indicate the selection of a common CDR-3 clonotype among the Igk light chains derived from both disease-free and diseased TCR1640 mice. Our study demonstrates the pre-clinical mobilization of the MOG-specific B cell response within the brain-draining cervical lymph nodes, and reiterate that pathogenic MOG antibodies are a poor biomarker of disease onset and progression.